Intracerebral implantation of human neural stem cells and motor recovery after stroke: multicentre prospective single-arm study (PISCES-2). Issue 4 (10th February 2020) - Muir, Keith W; Bulters, Diederik; Willmot, Mark; Sprigg, Nikola; Dixit, Anand; Ward, Nick; Tyrrell, Pippa; Majid, Arshad; Dunn, Laurence; Bath, Philip; Howell, Julian; Stroemer, Paul; et al.
Abstract : Background: Human neural stem cell implantation may offer improved recovery from stroke. We investigated the feasibility of intracerebral implantation of the allogeneic human neural stem cell line CTX0E03 in the subacute—chronic recovery phase of stroke and potential measures of therapeutic response in a multicentre study. Methods: We undertook a prospective, multicentre, single-arm, open-label study in adults aged >40 years with significant upper limb motor deficits 2–13 months after ischaemic stroke. 20 million cells were implanted by stereotaxic injection to the putamen ipsilateral to the cerebral infarct. The primary outcome was improvement by 2 or more points on the Action Research Arm Test (ARAT) subtest 2 at 3 months after implantation. Findings: Twenty-three patients underwent cell implantation at eight UK hospitals a median of 7 months after stroke. One of 23 participants improved by the prespecified ARAT subtest level at 3 months, and three participants at 6 and 12 months. Improvement in ARAT was seen only in those with residual upper limb movement at baseline. Transient procedural adverse effects were seen, but no cell-related adverse events occurred up to 12 months of follow-up. Two deaths were unrelated to trial procedures. Interpretation: Administration of human neural stem cells by intracerebral implantation is feasible in a multicentre study. Improvements in upper limb function occurred at 3, 6 and 12 months, but not in those with absent upper limb movement at baseline, suggesting a possible target population for future controlled trials. Funding: ReNeuron, Innovate UK (application no 32074-222145). Trial registration number: EudraCT Number: 2012-003482-18